The therapeutic potential of red radish microgreens in modulating inflammation and cancer pathways - Trina Ekawai Tallei; Nova Hellen Kapantow; Nurdjannah Jane Niode; Illah Sailah; Maghfirah Savitri; Muhammad Yamin Lahay; Jayanthi Barasarathi (CyTA - Journal of Food)
This review highlights the therapeutic potential of red radish microgreens (RRMs) as a nutrient-rich food with notable antioxidant, anti-inflammatory, and anticancer properties. Rich in bioactive compounds such as phenolic acids, flavonoids, glucosinolates, isothiocyanates, sulforaphane, and carotenoids, RRMs exhibit the ability to modulate key signaling pathways, including NF-κB, MAPK, JAK/STAT, TGF-β, SRC kinase, COX-2-PGE-2, and Wnt/β-catenin. These pathways regulate critical processes such as cell proliferation, angiogenesis, migration, and apoptosis, offering potential for inflammation and cancer mitigation. The review also explores the suitability of RRMs as space food, emphasizing their rapid growth, minimal resource requirements, and ability to support astronauts’ health by addressing oxidative stress, immune dysregulation, and inflammation in microgravity. While current evidence underscores their health-promoting effects, further in vitro and in vivo studies are essential to elucidate their molecular mechanisms and optimize their applications in medicine and space nutrition.